Diseño y desarrollo de un producto que permita la reducción del estrés térmico en el ganado bovino de la región de guaduas Cundinamarca - Rodríguez Castillo, Nelson Ignacio (Universidad Antonio Nariño, 2023)
According to the livestock context, in recent years global warming is a factor that is affecting not only plants but also animals that are exposed to solar radiation, the ICA (Colombian Agricultural Institute) is currently linked in the search for a solution, which can help the small producer in the implementation of a solution, which allows controlling this phenomenon associated with the heat that is not only affecting the livestock but also the pastures that they consume, the forage that due to photosynthetic radiation1 are dehydrating. (Livestock context, 2017) This climate impact is affecting producers of milk, meat, and breeders, in cattle